RLS Impedance Intelligence Control Algorithm for Wire Peeler of Robot in Complex Power Networks. (29th October 2020) - Xu, Xianjin; Hu, Shichao; Yan, Yu; Yang, Yuhang; Yang, Zhiyong; Chen, Haoda
Abstract : Considering the wire core which is easily damaged because of the instability of the power distribution robot during the process of peeling the insulation layer, we have proposed a cutting force tracking control algorithm based on impedance control that is suitable for the end peeling instrument. At present, the task requirement of sudden changes about environment stiffness cannot be accomplished by many impedance control approaches due to the complexity of working environment stiffness about power distribution robot; then, the Recursive Least Square (RLS) method was introduced into the impedance control algorithm to identify the cable insulation layer and cable core stiffness online to achieve accurate and stable tracking of the cutting force. Furthermore, the impedance control of peeling cable insulation layer and the proposed RLS method were simulated and tested contrastively, and the high-voltage cable peeling experiment was performed. The results of simulation and experiment showed that the force control algorithm based on RLS parameter identification still has good force tracking performance during the environment stiffness changes suddenly, and the steady-state error approaches zero, demonstrating the feasibility and effectiveness of the RLS impedance control algorithm, which has important practical significance for improving power distribution efficiency.